The Influence of Financial Literacy and Financial Attitude on Financial Satisfaction with Financial Management Behavior as a Mediating Variable - Maulana, Panji; Setiawati, Ira; Meiriyanti, Rita (INTERNATIONAL CONFERENCE OF ECONOMICS AND BUSINESS, 2025)
This research aims to examine The Influence of Financial Literacy and Financial Attitude on Financial Satisfaction with Financial Management Behavior as a Mediating Variable. The study employs a quantitative approach, using a questionnaire as the research instrument. The sample consists of 96 respondents, selected through purposive sampling with criteria including micro and small industries in Semarang City that have already adopted e-wallets such as Gopay, OVO, Dana, ShopeePay, and Link Aja. The data were analyzed using the Smart PLS 3 method. The research data have passed validity and reliability tests, indicating that the data meet the necessary model requirements to proceed with hypothesis testing. The findings of the study reveal that: (1) Financial Literacy influences Financial Satisfaction, (2) Financial Attitude influences Financial Satisfaction, (3) Financial Literacy influences Financial Management Behavior, (4) Financial Attitude influences Financial Management Behavior, (5) Financial Satisfaction does not influence Financial Management Behavior, (6) Financial Literacy does not influence Financial Satisfaction when mediated by Financial Management Behavior, and (7) Financial Attitude does not influence Financial Satisfaction when mediated by Financial Management Behavior.